A DISCUSSION ON THE ANALYTIC AND SYNTHETIC DISTINCTION - Mahmud Layan Hutasuhut (BAHAS, 2010)
This paper is an attempt to give an account of the analytic-synthetic distinction both inside and outside of physical theory, which is sufficiently non-technical to be followed by a reader whose background in science is not extensive, but it has been necessary to consider problems connected with physical science in order to bring out the features of the analytic-synthetic distinction that seem to be the most important. This paper, then, fights on two fronts; it tries to ‘defend’ the distinction since there is somewhat newer danger of denying its existence altogether, while attacking its extensive abuse by philosophers, which is nevertheless an error. Key words: Analytic, synthetic, distinction